The Essence And Stages Of Development Of The "Green" Economy Concept - Abdikarimova Aynura Abay qizi (Genius Journals, 2024)
This article shows the essence of the green economy concept, the stages of sustainable development, and the main task of the "Green" economy is to change production and consumption processes in accordance with ecological standards
Keywords: Green economy; ecological crises; concept of